Biomass Estimation and Distribution of Nutrients in Five Different Aged Eucalyptus grandis Plantation Ecosystems in Kerala State - Tandon, V. N.; Pande, M. C.; Singh, Rajender (Indian Forester, 1988)
Above and below-ground biomass and distribution of nutrients of five different aged stands of Eucalyptus grandis have been discussed. Correlation coefficient and regression models were worked out separetely for each biomass component, total above-ground and total biomass. Among the predictor variables tried, D.B.H. was found to be the most reliable parameter for prediction of biomass. The results were significant at 0.01% level of probability. The total standing biomass of these plantations ranges between 65 t/ha to 302 t/ha. An estimate has been made of the quantity of nutrients immobilized in the crop. The quantity of nutrients removed permanently from the site has also been discussed. Leaving foliage and debarking at the site has been suggested to check the deterioratlon of the site to some extent.